Desafios da inclusão de pessoas com deficiência: um projeto de responsabilidade social da Universidade Federal de Santa Catarina - Alessandra de Linhares Jacobsen; Luís Carlos Cancellier de Olivo; Nilton Orany Bonatte Cardoso; Ricardo Uliano dos Santos (Revista Gestão Universitária na América Latina)
This article aims to analyze the performance of Federal University of Santa Catarina (UFSC) in including disability people (DP) at work, under the social responsibility concept. To achieve this goal, it was used the qualitative, descriptive and applied research, the case study, a field, literature and documental research. The data collection, occurred in 2014, involved the use of the direct observation and a questionnaire applied to the 44 disabilities workers of UFSC. Data were analyzed considering the qualitative approach. But with the structured questionnaire it was also possible to obtain the frequency of view of research subjects. As a result, it was obtained the perception of the DP workers about the institutional performance in including them at work; it were identified actions taken by UFSC, and by its multidisciplinary team, in the context of the social responsibility and inclusion of disability people (DP) at work; and finally, it was proposed alternative actions to consolidate the social responsibility management and the inclusion of disability people (DP) at UFSC. The study concludes that UFSC has positive aspects about fomenting the inclusion of its disability works, but there are also others, in the context of accessibility, which still need to be improved.